Benzothiazole derivatives based colorimetric and fluorescent probes for detection of amine/ammonia and monitoring the decomposition of urea by urease - Zheng, Shiyue; Fang, Yu; Chen, Yahui; Kong, Qing; Wang, Fang; Chen, Xiaoqiang (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2022)
[Display omitted] •Two probes have instant ratiometric and colourimetic response to amines.•Highly sensitive amine probes were based on strips and electrospun membranes.•The fluorescent probes provide reusability for monitoring amine vapours.•The demonstrated probes could be applied in monitoring urea decomposition. Amines play critical roles in chemical, agrochemical and pharmaceutical industries. However, volatile amine vapours cause widespread pollution and threaten human health. An efficient, highly sensitive and recyclable sensor for monitoring amine vapours is highly demanded. Typically, 2-(2-hydroxy-5-methyl) benzothiazole (HBT) derivates exhibit excellent aggregation-induced emission (AIE) phenomena in keto form originated from a unique excited-state intramolecular proton transfer (ESIPT) process. In this work, we have designed and synthesized two HBT-based fluorescent probes for ratiometric detection toward amine vapours and ammonia. In addition, the detection limits for ammonia were calculated as 226 ppm and 13 ppm respectively. Additionally, the test strips and electrospinning film dopped with fluorescent probes were utilized to recognize amine vapours and ammonia colorimetric with high sensitivity in solid states. According to the above characteristics, probes could monitor the biological activity of urease conveniently and rapidly.